Psychometric evaluation of Persian version of the oral presentation evaluation scale in nursing students - Tahmine Rahmatkhah; Rajab Dashti-Kalantar; Nazila Vosoghi; Alireza Mirzaei; Saeid Mehri (BMC Nursing, 2024)
Abstract Background Nurses should possess the ability to deliver concise oral presentations. Strong oral presentation skills can improve the quality of nurse-client communication, enhance teamwork among healthcare professionals, and contribute to professional development, leadership, and promotion. This study aimed to determine psychometric evaluation of the Persian version of the oral presentation evaluation scale in nursing students. Methods The study aimed to translate the oral presentation evaluation scale (OPES) into Persian using the standard translation and re-translation method. After the translation, the scale was distributed among 474 nursing students of various levels using the available sampling method. The scale’s reliability was assessed using Cronbach’s alpha coefficient and test-retest repeatability. The construct validity was determined using the confirmatory factor analysis. Results The Persian questionnaire consists of 15 items and is divided into three categories: accuracy of content, effective communication, and speech clarity. The overall score for the content validity index (S-CVI) was 0.94. The three-factor questionnaire’s fitness indices were RMSEA = 0.070, comparative fit index (CFI) = 0.96, goodness-of-fit index (GFI) = 0.91, and adjusted goodness-of-fit index (AGFI) = 0.88. The intra-cluster correlation index (ICC) was 0.965, and Cronbach’s alpha was 0.875. Conclusion The study found that the 15-item oral presentation evaluation scale Persian Survey is reliable for assessing nursing students’ oral presentation skills.